Bettered strength and fracture behavior of plain weave carbon fiber reinforced epoxy laminate with open hole under the influence of hole shape/size and strain rate - Rzgar Mhammed Abdalrahman; Sarkawt Rostam; Hameed Dwech Lafta (Results in Engineering)
The plain weave Carbon Fiber Reinforced Epoxy (CFRE) composite components require various hole shapes or cut-outs for joining, while undesirable notch shapes may arise during application. The literature has not adequately addressed the sensitivity of this composite to open holes. The novelty lies in defining the optimal effects that provide bettered Hole Tensile Strength (HTS) of this composite during applications. Nine test trials were designed based on Taguchi's orthogonal array L9 to experimentally investigate the influence of hole shape/ size, and strain rate, on the HTS and damage behavior of the proposed composite. Results were analyzed by Analysis of Variance (ANOVA). Simulation tests were performed on ANSYS/workbench with actual material properties and boundary conditions. Numerical results presented the gradual increase of strain from the edge toward the hole's root which becomes more rapid at the hole's tips, while notch shape has an obvious effect on in-plain and through-thickness strain distributions. Also, the ultimate elastic strain of 0.0275 mm/mm, 0.0331 mm/mm, and 0.055 mm/mm occurs respectively at the tips of circular, square, and rhombic notches. Experimental results presented the effectiveness of 46.7 %, 40 %, and 6.4 %, for hole size/shape, and strain rate on HTS, respectively. Also, defined the bettered combination of test factors of the circular-shaped notch of 8 mm size and 0.022 s−1 strain rate.